2018
DOI: 10.17159/2310-3833/2017/vol48n1a7
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy students' experiences and perceptions of culture during fieldwork education

Abstract: Background: Understanding a client's culture allows practitioners to consider the planning of intervention and allows for a client centred approach to be provided. During fieldwork education occupational therapy students can face the challenge of other cultural practices, standards, morals and ways of life coming into conflict with their own.Purpose: There is minimal South African literature discussing the challenges and supporting factors that assist students in becoming culturally competent across cross-cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
2
9
0
7
Order By: Relevance
“…Similar ndings have been reported by a study conducted by Inge Sonn & Nikki Vermeulen (2018) [5] , where the main theme derived from the analysis was, culture is easily dened but not easily described. The participants reported that they faced difculty in communicating with the client due language barrier; i.e.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar ndings have been reported by a study conducted by Inge Sonn & Nikki Vermeulen (2018) [5] , where the main theme derived from the analysis was, culture is easily dened but not easily described. The participants reported that they faced difculty in communicating with the client due language barrier; i.e.…”
Section: Discussionsupporting
confidence: 85%
“…The main theme emerged from the analysis was," Culture is easily dened but not easily described". (Inge Sonn and Niki Vermeulen, 2018) [5].…”
Section: Introductionmentioning
confidence: 99%
“…With more significant items in the fieldwork setting than academic, results indicated that students perceived fieldwork prompted greater growth in professional behaviors than did the academic setting, possibly due to real-world experience. Sonn and Vermeulen (2018) also found that fieldwork experiences prompted growth in professionalism, in the area of cultural competence. These authors speculated that exposure, reflection, and attitude accounted for such growth.…”
Section: Discussionmentioning
confidence: 91%
“…Occupational therapy (OT) educators recognize the need to assist students to progress along a continuum of behavior that leads them toward professionalism. Reflection is often seen as a tool assisting in that process (Adam, Peters, & Chipchase, 2013;Anderson et al, 2014;Brown, Williams, & Etherington, 2016;Smith & Trede, 2013;Sonn & Vermeulen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One survey respondent expressed concern about the majority of her classmates coming from middle to upper middle income backgrounds and worried how this may impact her fellow classmates' learning and practice with low income individuals. Graduate programs, specifically occupational therapy programs, often strive for representation of individuals from diverse backgrounds and experiences, yet may not provide students with adequate exposure to social and cultural diversity and cultural awareness training (Sonn- De Minck & Vermeulen, 2018). Students who lack understanding of the complexity of their patients' backgrounds and life experiences, such as low income challenges, may be less able to provide effective therapy (Naidoo & Van Wyk, 2016).…”
Section: Individual Experiences With Low Incomementioning
confidence: 99%